Effects of Aluminium Chloride Exposure on the Histology of lungs of Wistar Rats - A.A. Buraimoh and S.A. Ojo (Journal of Applied Pharmaceutical Science, 2013)
Aluminium is presents in many manufactured foods and medicines and is also added to drinking water for purification purposes. The lungs consist essentially of; the spongy respiratory tissue in which gaseous exchange occurs between blood and air, and a branching system of air tubes called bronchioles and bronchi which 'pipe' air into and from the pockets and passageways of the spongy respiratory tissue. The purpose of this study was to evaluate the possible effects that aluminium chloride exposure could have on the histology of lungs of wistar rats. Twenty wistar rats were used for this study. They were well fed with grower mash, provided with adequate water and kept under good ventilation. The wistar rats were divided into five groups as follows: Group I was the control, group II was given 475mg/Kg, group III received 950mg/kg, group IV received 1,425mg/kg and group V received 1,900mg/kg of aluminium chloride through oral intubation for period of eight weeks. The wistar rats were humanely sacrificed, the lungs removed, fixed, processed and stained with Haematoxylin and eosin. Photomicrographs of the lungs showed congested blood vessels in the aluminium treated groups. Based on our observations, we therefore conclude that aluminium chloride exposure was detrimental to the histology of lungs.
Keywords: Aluminium Chloride,Histology,Lungs and Wistar Rats.